The effectiveness of sociodrama intervention on anxiety and avoidance of problem solving in children - alikhani, hoda; Houshmand Khayat, Amir Hossein; Banshi , Zainab (Iranian Journal of Neurodevelopmental Disorders, 2023)
Introduction: The aim of this study was the effectiveness of sociodrama intervention on anxiety and avoidance of problem solving in children. Methods: Research method in this study was a single-subject of AB experimental designs. The statistical population consisted of all children with social anxiety disorder 6 to 7 years that attended psychological centers in Tehran in 2021. Among them, 5 children with social anxiety disorder (two boys and three girls) were selected based on inclusion and exclusion criteria and by purposive sampling. Sociodrama intervention was performed for each child in 10 sessions. The research instrument included Social Behavior Checklist (Made by a researcher). Data were analysed using visual analysis at both within-condition and between-condition levels. Findings: Research findings showed that sociodrama intervention improved anxiety and avoidance in children in problem solving; So that the scores in 10 sessions of intervention had a significant decrease compared to the baseline scores. The total recovery rate in anxiety and avoidance of problem solving was 67.01 percent. Conclusions: Based on the findings, it can be concluded that the sociodrama intervention can improve the anxiety and avoidance of problem solving in children. Therefore, family and educational institutions, psychological and counseling services centers can benefit from sociodrama intervention to reducing anxiety and avoidance of problem solving in children.